EFEKTIFITAS PROMOSI KESEHATAN MELALUI VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG BAHAYA ROKOK - Hadi, Sulistiowati Kusuma; Aisyiah, Aisyiah; Widiastuti, Susanti (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
Smoking behavior of the youth is a high stakes problem in Indonesian. This issue will profound impact on a youth’s future, for the youth began to consume cigarettes out of curiosity and the influence of the the environment. Smoking behavior in adolescents results from a lack of information. It is obtained that affects the level of knowledge and youth's attitudes regarding dangers a cigarette. This research aims to see the effectiveness of health promotions through the animated videos to the level of adolescents' knowledge and attitudes about the dangers of smoking. The study use quasi method of experimenting with one group pre-test and post-test without control group design. The number of samples in this study is 111 sampling. The instruments in this study use questionnaires that have been examined as validity and reliability as well as visual audio media. The questionnaire consists of 20 knowledge questionnaires with cronbach’s.alpha that is 0,971; and 20 questionnaires with a cronbach’s.alpha 0,952. The statistic test that was used is that wilcoxon signed rank test. The research show that there is a significant difference between the scores of knowledge and the attitudes of the youth before and after being given interventions through audio media visual (animated video) on the dangers of cigarettes. At the knowledge score that is p value = 0,000 and their attitude is that p value = 0,000. Then it may be concluded that visual media (animated videos) can enhance the knowledge and attitude of the youth, thereby improving knowledge and attitude.